Political leaders' socioeconomic background and fiscal performance in Germany - Bernd Hayo; Florian Neumeier (Philipps-University Marburg, Faculty of Business Administration and Economics, 2011)
This paper investigates whether the socioeconomic status of the head of government helps explain fiscal performance. Applying sociological research that attributes differences in people's ways of thinking and acting to their relative standing within society, we test whether the social status of German prime ministers can help explain differences in fiscal performance among the German Laender. Our empirical findings show that the tenures of prime ministers from a poorer socioeconomic background are associated with higher levels of public spending and debt financing.
Keywords: E61; E62; H11; H72; 330; leadership; socioeconomic status; fiscal policy; public spending; public deficit; Regierungschef; Sozialer Status; Finanzpolitik; Länderfinanzen; Deutschland